Citizenship-as-competence, what else? Why European citizenship education policy threatens to fall short of its aims. (May 2022) - Joris, Margot; Simons, Maarten; Agirdag, Orhan
The topic of citizenship education and the promotion of democratic citizenship in schools has risen to the top of educational policy agendas in Europe over the past three decades. This rise in attention, however, appears to be accompanied by an apparent lack of attention to the specific manner in which citizenship, education and the assumed relationship between both are currently conceptualised and understood in this policy context. The currently dominant notions of citizenship education centre around a concept of citizenship-as-competence, illustrating a certain assumption of equivalence between citizenship and formal education in schools, without further elaborating on this assumption. By means of a critical re-reading of key European educational policy texts referring to citizenship education, and their use of the key concepts of citizenship and education, our analysis shows how the competence-based approach to citizenship education in European educational policymaking entails tensions with its own assumptions, therefore falling short of its own proclaimed purpose of emancipating young people in Europe to become autonomous, engaged and critical democratic citizens.